The State of Loneliness among Migrating Students: The Effect of Psychological Well-Being and Religiosity - Laksmidara, Mahadewi; Nashori, Fuad (International Journal of Islamic Educational Psychology, 2022)
Being separated from their parents causes many migrated students to experience loneliness, not to mention that their age range is prone to it. Therefore, this study aims to determine the effect of psychological well-being and religiosity on loneliness and isolation in migrated students using ex post facto quantitative research methods. Respondents to this study were active 213  migrated students in several universities in Yogyakarta, Indonesia. Their ages ranged from 18 to 24. The measuring instruments used were UCLA Loneliness Version 3 (α 0.942), the Psychological Well-being Scale (α 0.776), and the Centrality of Religiosity Scale (α) 0.876). The data analysis technique used was multiple regression. The results indicated a significant negative effect of psychological well-being on loneliness and no significant negative impact of religiosity on loneliness in migrated students. Psychological well-being and religiosity contributed 58.2% to influencing the loneliness variable. The study concluded that psychological well-being made migrated students experience less loneliness when they were far away from their hometowns.